Bridging Law, Ethics, and Learning the Urgent Need for Electronic Medical Record Integration in Clinical - Marsa Zaidan; Siti Soekiswati; Imronudin Imronudin (Jurnal Ilmiah Global Education, 2026)
The rapid advancement of health information technology has accelerated the transition of medical documentation from traditional paper-based records to Electronic Medical Records (EMRs). In the context of medical education, clinical students are expected to master accurate, efficient, and ethically responsible documentation practices as part of their professional competencies. However, the implementation of EMRs within teaching hospitals and medical schools continues to face significant challenges, particularly related to legal uncertainty, patient privacy protection, and the absence of comprehensive institutional policies governing student access and responsibility. This literature review aims to synthesize current evidence regarding the legal and ethical implications of EMR use by medical students and to assess the urgency of integrating structured EMR training into undergraduate and clinical medical curricula. A qualitative literature review was conducted using 22 relevant national and international studies published within the last decade. The findings indicate that EMR utilization contributes positively to the development of students’ clinical documentation skills, clinical reasoning, and readiness for professional practice in digital healthcare environments. Nevertheless, unresolved issues remain, including the legal status of student-generated medical records, potential violations of patient confidentiality, and unclear liability frameworks when documentation errors occur. Additional barriers identified include limited formal training, restrictive access policies, and inconsistent supervision during clinical rotations. This review highlights the urgent need for clear national regulations, standardized institutional policies, explicit education on digital health ethics, and structured EMR training programs within medical education. Such measures are essential to ensure legal compliance, safeguard patient rights, and adequately prepare future physicians to practice responsibly in increasingly digitalized healthcare systems.